Produção de vídeos caseiros pelos próprios alunos como estratégia para melhorar a aprendizagem dos conceitos abordados nas aulas regulares de Física no Ensino Médio e com ênfase no registro das atividades propostas - Marinovic, Jorge Antonio (2012)
This work presents the results of a study about the efficience of home video productions by own students to get a better learning in Physics by the understanding of some important teacher´s assignments at Senior High School. The students were taught to elaborate the scripts, making off and other basic filming techniques, but the most important thing was to encourage them to engage into research and be creative in their videos. The resulting overall product resulted showed in the videos gave us the opportunity to evaluated the knowledge working as an alternative for the written assignments demand or other kinds of records like experiment records and science center visits records, which most of the students making use the traditional copy and paste rules from the Internet. The work was developed for a year and half, when we did five activities involving since videos production until its exposure and discussions done by the classmates. Teacher s suggestions for the doing videos depend on the subjects studied in the bimestrial. The work was done in first, second and third Senior High School grades. The results allowed us to evaluate the efficiency of different ways of asking assignments for the students, which were done orally, written, given a script or by videos, besides giving support to teachers use as a methodological approach more efficient. We gather that when it s used by the right way, the video home productions done by the students themselves showed to be good, because it can motivate them to research and work like a group, at the same time as become clear how poor are the other students participation and interest. In this situation, the videos productions are substandard, with no good techniques or contents qualities. The spontaneous student testimonies showed that they were motivated to do the videos, and our observation of the questions and students talks during the class showed that those who really did the video production increased their knowledge about the critical analyses phenomenon studied. The videos are on the Internet, with free access and the addresses are in the attachment. Another result for this article was the educational material folder. It s a short introductory manual with instructions for concerned and willing teachers incorporate this approach in their teaching plans.